The Influence of Islamic Work Ethics and Affective Commitment on Teacher Performance Mediated by Job Satisfaction: Case in Insan Cendekia Boarding School (ICBS) Payakumbuh - Supriyansyah, Mekri; Harif Amali Rivai; Rahmi Fahmy (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study examines the influence of Islamic Work Ethics (IWE) and Affective Commitments (AC) on Teacher Performance (TP) at Insan Cendekia Boarding School Payakumbuh, with Job Satisfaction (JS) as a mediating variable. A quantitative approach was employed, collecting data from 152 randomly selected teachers using structured questionnaires. The data were analyzed using SmartPLS 4.0, encompassing descriptive analysis, measurement and structural model evaluations, and hypothesis testing. The results reveal that Islamic work ethics significantly improve job satisfaction but do not directly affect teacher performance. However, job satisfaction mediates the relationship, enabling Islamic work ethics to enhance performance indirectly. Similarly, affective commitments positively influence both job satisfaction and teacher performance, with job satisfaction playing a significant mediating role. These findings underscore the critical role of job satisfaction in amplifying the impact of ethical practices and emotional commitment on teacher performance. The research highlights the need for a holistic approach in educational management that integrates Islamic values, emotional engagement, and teacher well-being to foster a high-performing environment. Practical implications include promoting job satisfaction through fair compensation, professional growth opportunities, and a supportive work atmosphere to ensure teacher excellence in boarding schools.